Technical Efficiency Measurement of the Teaching Function in the Undergraduate Attendance Programs at Universidad Militar Nueva Granada - Buitrago Suescún, Oscar Yecid; Espitia Cubillos, Anny Astrid; Linares Cárdenas, Daniela (TECCIENCIA, 2015)
Public higher education institutions in Colombia have limited resources (and often insufficient), so it is crucial to use them adequately to fully achieve their mission objectives. This paper presents a measurement and analysis of the technical efficiency of teaching, a core mission of the undergraduate attendance programs at Universidad Nueva Granada. The method used is data envelopment analysis, as it provides relative efficiency scores of the units under study and it also gives additional information of the reference peers. This allows formulating improvement plans for the university management. Two study scenarios were defined: the first includes inputs and desirable outputs and the second takes into account undesirable outputs. Performance was analyzed for six consecutive semesters from the year 2011 and the corresponding Malmquist indices were calculated. The results are encouraging since they indicate that 30.76% of the programs are 100% efficient in all periods regardless of the scenario in which they were measured.